Produtos alternativos no manejo de doenças da videira - Leite, Carla Daiane (2017)
The search for substances capable of acting in the defense of plants is a necessity for the management of diseases in the vitiviniculture organic. In the first part of the tests, 0 concentrations were evaluated; 3; 6; 9 and 12% aqueous extract of grape marc (AEGM), standard treatments Bordeaux mixture (BM) 1% and Saccharomyces cerevisae (SC) (1 mL L-1) in the control of mildew (Plasmopara viticola) in leaf and in vine plants, as well as the induction of β-1,3-glucanases and chitinase in vines and the synthesis of phytoalexins in sorghum mesocotyls. The chemical composition of the grape marc and the chromatographic profile of the AEGM at 12% were measured with a purpose of identification with anti-mildew action. The AEGM applied in foliar discs in the concentration of 12% reduced in more than 50% the severity of the mildew. In field conditions, the extract was efficient in a manner analogous to the CB standard. In addition, it induced the activity of the defense enzymes β-1-3- glucanases and chitinase 24 and 48 hours after the onset of the disease's first symptoms and phytoalexin synthesis. The minerals identified as phosphorus, sulfur, potassium, calcium and magnesium and the phenolic compounds galic, caffeic and vanillic acids; the catechin and epicatechin flavonoids. In the second part of this work, the Brassica napus in the form of aqueous extract (AEB) without control of the media and as sachets (0; 0.8; 1.7; 2.55 and 3.4g), releasing volatile compounds without raw carbon control in vivo and in vitro is used. As extract concentrations as their previous works. It was verified that the aqueous extract of B. napus harmed the development of mildew by controlling between 20 and 30% in relation to the control treatment, when 6% of extract was used in the two cycles of grapevine cultivation. Canola meal possibly released volatile compounds at all concentrations capable of reducing B. cinerea mycelial growth and conidia production as gray mold on cv. Rubi.